2017
DOI: 10.1111/jcmm.13212
|View full text |Cite
|
Sign up to set email alerts
|

Dl‐3‐n‐butylphthalide attenuates acute inflammatory activation in rats with spinal cord injury by inhibiting microglial TLR4/NF‐κB signalling

Abstract: In this study, we examined the neuroprotective effects and anti‐inflammatory properties of Dl‐3‐n‐butylphthalide (NBP) in Sprague‐Dawley (SD) rats following traumatic spinal cord injury (SCI) as well as microglia activation and inflammatory response both in vivo and in vitro. Our results showed that NBP improved the locomotor recovery of SD rats after SCI an significantly diminished the lesion cavity area of the spinal cord, apoptotic activity in neurons, and the number of TUNEL‐positive cells at 7 days post‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Similar findings demonstrated that microglia activation had resulted in inflammatory response in rats following SCI, and Dl-3-n-butylphthalide may have neuroprotective and anti-inflammatory properties in the treatment of SCI by inhibiting the activation of microglia via TLR4/NF-kappaB signaling. 20 Next, astrocytes were activated to further enhance the inflammation response. 32 , 33 The finding showed after SCI, reactive astrocytes had undergone M1 microglia-induced necroptosis, partially through TLR/MyD88 signaling, and suggested that inhibiting astrocytic necroptosis may be beneficial for preventing secondary SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings demonstrated that microglia activation had resulted in inflammatory response in rats following SCI, and Dl-3-n-butylphthalide may have neuroprotective and anti-inflammatory properties in the treatment of SCI by inhibiting the activation of microglia via TLR4/NF-kappaB signaling. 20 Next, astrocytes were activated to further enhance the inflammation response. 32 , 33 The finding showed after SCI, reactive astrocytes had undergone M1 microglia-induced necroptosis, partially through TLR/MyD88 signaling, and suggested that inhibiting astrocytic necroptosis may be beneficial for preventing secondary SCI.…”
Section: Discussionmentioning
confidence: 99%
“…All surgeries were performed by the same surgeon following the methods outlined previously. 14 , 20 Briefly under aseptic conditions, the T10 spinal cord segment was fully exposed by T9-T11 dorsal laminectomies leaving the dura intact using an operating microscope (M500-N, Leica, Heerbrugg, Switzerland). Subsequently, compressive injury was induced by a 2-minute compression SCI using a 10 g aneurysm clip (5.0 mm*0.8 mm, Kent Scientific, Torrington, CT, USA; Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The inflammatory response in the injured spinal cord is a key mechanism mediating the secondary injury stage after SCI (2,25). The cells at the site of injury trigger the inflammatory response through the activation of multiple receptors, including TLR4, in immune-competent cells, neurons and astrocytes (26). These receptors promote the activation of NF-κB, a multifunctional transcription factor that controls several pro-inflammatory and stress responses, which may ultimately induce apoptosis, neuronal degeneration and disease progression (27).…”
Section: Discussionmentioning
confidence: 99%
“…Based on its multi-target therapeutic properties, NBP has demonstrated an important role in a number of nervous system diseases, including amyotrophic lateral sclerosis (10), Parkinson's disease (11) and VD (12), as well as models of Alzheimer's disease (13). Studies have also demonstrated that multiple mechanisms are involved in the neuroprotective effects of NBP, including anti-inflammatory effects, suppression of oxidative stress, inhibition of platelet aggregation and anti-apoptosis (14)(15)(16)(17). However, little is known about the protective role of NBP against chronic ischemia-induced excessive autophagy in VD.…”
Section: Introductionmentioning
confidence: 99%